Ibu Hamil “Kemel” Pada Etnis Gayo Di Kecamatan Blang Pegayon Kabupaten Gayo Lues, Aceh - Niniek Lely Pratiwi; Yunita Fitrianti; Syarifah Nuraini; Tety Rachmawati; Agung Dwi Laksono (Buletin Penelitian Sistem Kesehatan, 2019)
The unique and enormous culture of concealed pregnancy or “Kemel” in Gayo ethnic, low coverage of antenatal care for pregnant women in health workers and high numbers of neonatal mortality, and infection in infants with low birth weight were social determinants of health issues existing in Aceh. These were urgently observed to fi gure out solution in reducing low examination of antenatal care by pregnant women in Gayo. Increasing the interest of researchers to conduct this research. This descriptive study was based on socio-cultural phenomena that aff ect a “Kemel” pregnant woman. The results showed ‘Kemel’ vulnerability perceptions were indicated by keeping the pregnancy as a secret in case of being used by those who do not like their pregnancies. ’Kemel’ perceived severity aff ects the safety of women pregnancies. Pregnant women may get some threats such as: malnutrition, lack of calorie energy, anemia, newborn with low birth weight, premature newborn, and infectious diseases. “Kemel” cues to action, pregnant women check theirpregnancies after 5 months pregnancy to a traditional birth attendant. Soon after TBA claimed their pregnancies, they refer to midwives. This the reason why examination of antenatal care were very low. Family role in the social structure, the culture of the Gayo, parents-in-law and parents of pregnant women, have a great contribution in making decisions such as pregnancy, childbirth and postpartum cares. A marriage tradition of the Gayo, was when a woman pawned into a part of male family, she must follow its habits and traditions. Thus, intervention by forming an agent of change are highly recommended by involving parent in law. Abstrak Tingginya budaya merahasiakan kehamilan/”Kemel”pada etnis Gayo, rendahnya cakupan antenatal care ibu hamil pada petugas kesehatan dan tingginya kematian neonatal, infeksi pada bayi dengan Berat badan lahir rendah, menambah ketertarikan peneliti untuk melakukan penelitian ini. Metode penelitian adalah kualitatif, peneliti menganalisis berdasarkan fenomena sosial budaya yang dapat mempengaruhi seorang ibu hamil “Kemel”. Hasil menunjukkan Persepsi kerentanan ‘Kemel’, dengan merahasiakan kehamilannya, takut diguna-guna orang lain yang tidak suka kehamilannya. Perceived severity Kemel mempengaruhi keselamatan kehamilannya, ancaman pada ibu hamil: gizi kurang, Kurang Energi Kalori, anemia dan bayi dengan Berat Badan Lahir Rendah/BBLR, bayi lahir prematur dan serangan penyakit infeksi pada ibu hamil. Cues To Action Kemel, periksa kehamilan saat kehamilan berusia 5 bulan pada bidan kampong, setelah bidan kampong menyatakan hamil ia baru pergi ke bidan, hal inilah yang menjadi salah satu penyebab rendahnya pemeriksaanantenatal care pada ibu hamil. Peran keluarga dalam struktur sosial, budaya masyarakat Gayo, Mertua dan orang tua bumil sangat besar dalam menentukan keputusan segala sesuatu yang berkaitan dengan keputusan dalam perawatan kehamilan, persalinan dan perawatan nifas. Suatu tradisi perkawinan masyarakat Gayo, perempuan sudah tergadai menjadi bagian besar keluarga pihak laki laki, ia mengikuti kebiasaan dan tradisi keluarga laki laki, sehingga bila membentuk agen perubahan perlu mempertimbangkan peran mertua.